Understanding Women Employees’ Satisfaction in the Automotive Sector: Challenges in a Male-Dominated Field - Amin, Grace; Henakin, Brigitha Queenkesya (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
The rising participation of women in the workforce has recently become a topic ofsignificant debate, particularly regarding the intricate balance between professional andfamilial responsibilities. This study seeks to elucidate the effects of workload stress,perceived organizational support, and work-family conflict on work-life balance, with jobsatisfaction as a mediating variable. Utilizing Structural Equation Modeling (SEM) toanalyze data from 254 valid respondents, the research tested ten hypotheses. Out of these,four hypotheses were substantiated, while six were not supported. Specifically, thehypotheses concerning the impact of perceived organizational support on work-lifebalance, the effect of work-life balance on job satisfaction, and the role of perceivedorganizational support in influencing job satisfaction—both directly and through work-life balance—were not validated.Keywords: Workload, Perceived Organizational Support, Work-family conflict, Work-life balance, Jobsatisfaction.